(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The research aimed to identify the level of use of smart device applications (Tik Tok platform), the level of anxiety among children and adolescents, and to reveal the existence of a statistically significant effect at a significance level (0.05≥α) for smart device applications on the phenomenon of anxiety among children and adolescents. The research community consisted of a group of children and adolescents. The research sample included (161) individuals. The researcher used the descriptive method as a research method, and used the questionnaire as a research tool. The research reached a number of results, the most important of which are: smart device applications (Tik Tok platform), and the level of anxiety among children and adolescents came with a response rate (very low), and the existence of a statistically significant positive effect of smart device applications on the phenomenon of anxiety among children and adolescents. The research recommended many recommendations, the most important of which were: preparing awareness programs for children and adolescents on how to manage the time of using social networking sites, and encouraging children and adolescents to communicate socially and form social relationships.